FINANCIAL RISK MANAGEMENT IN INVESTMENT PROJECTS: BUILDING A PREDICTIVE MODEL BASED ON BIG DATA - Elnaza Kassymkhanova (Scholar Express Journals, 2025)
In the conditions of unstable financial markets, effective risk management is the key to successful investments. This article is devoted to the use of Big Data and machine learning technologies to create a predictive model capable of assessing and reducing financial risks. An algorithm for combining data from various sources is described and the results of testing the model on real investment examples are demonstrated.
Keywords: financial risks; investment projects; Big Data